Early warnings are too late when parameters change rapidly - Rohit Radhakrishnan; Induja Pavithran; Valerie Livina; Jürgen Kurths; R. I. Sujith (Scientific Reports)
Abstract Tipping (or sudden transition) from a desirable state to an undesirable one can result in catastrophic changes, affecting natural environments, human societies and economies. Early warning signals (EWSs) are developed to forewarn such an impending tipping. However, when control parameters are varied fast, we observe that EWSs detect an impending tipping past bifurcation points; this questions the applicability of EWSs in preventing tipping. At the same time, the fast rate of change of parameter delays the actual tipping event, providing a borrowed window of safe operation. This delay in tipping offers a window for prevention through swift action. We demonstrate instances of both successful and unsuccessful preventions, in a paradigmatic thermoacoustic system—a horizontal Rijke tube. This work highlights the interplay of warning time, choice of prevention action and rate of variation of parameters in EWS-based prevention of tipping.